STRATEGI PERENCANAAN KEUANGAN DAERAH MENUJU GOOD GOVERNANCE - Sunarko, Muhammad Rofiq (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2006)
ABSTRACT Good governance can be achieved by the implication of the regional financial planning strategies, that consist of the improvement of the regional financial management mechanisms and the improvement of the territorial financial accounting system. Hence, an improvement have to be done in all phases i.e. planning, implication, and controlling phases. The development of the information technology can also support good governance achievement, i.e. by applying e-government (e-govt) as a mean to support and control the government’s role.   Keywords: good governance, regional financial management mechanisms, territorial financial accounting system,     e-government